Susceptibility vessel sign on MRI predicts better clinical outcome in patients with anterior circulation acute stroke treated with stent retriever as first-line strategy. (28th August 2018) - Bourcier, Romain; Hassen, Wagih Ben; Soize, Sébastien; Roux, Pascal; Labreuche, Julien; Kyheng, Maeva; Tisserand, Marie; Rosso, Charlotte; Blanc, Raphael; Piotin, Michel; Derraz, Imad; Boulouis, Gregoire; et al.
Abstract : Background: Susceptibility vessel sign (SVS) can be a useful MRI biomarker of an occlusion but its relationship with clinical outcomes of acute ischemic stroke (AIS) is yet to be fully elucidated. Objective: To investigate SVS in relation to the clinical outcomes after mechanical thrombectomy using a stent retriever (SR) as first-line approach in patients with AIS. Material and methods: We included patients with a first-line SR approach for anterior AIS from the the Contact Aspiration vs Stent Retriever for Successful Revascularization (ASTER) and THRombectomie des Artères CErebrales (THRACE) trials when both baseline imaging of SVS and 90-day modified Rankin Scale (mRS) scores were available. Patients were assigned to two groups based on the presence of an SVS (independent core laboratory), and the overall distributions of the mRS score at 90 days (shift analysis) and clinical independence (mRS score ≤2) were compared. Results: 217 patients were included and SVS was diagnosed in 76.0% of cases (n=165, 95% CI 70.4% to 81.7%). After adjustment for potential confounders, SVS+ was significantly associated with 90-day mRS improvement (adjusted common OR=2.75; 95% CI 1.44 to 5.26) and favorable outcome (adjusted common OR=2.76; 95% CI 1.18 to 6.45). Conclusion: Based on results for patients of the ASTER and THRACE trials receiving first-line SR treatment, SVS was associated with lower disability at 3 months. Large prospective studies using MRI-based thrombus evaluation are warranted.